Relativistic Prolapse-Free Gaussian Basis Sets of Double- and Triple‑ζ Quality for d‑Block Elements: (aug-)RPF-2Z and (aug-)RPF-3Z - Julielson dos Santos Sousa (20205635) (2025)
This study introduces new series of relativistic prolapse-free Gaussian basis sets of double- and triple-ζ quality (RPF-2Z and RPF-3Z), specifically designed for all known d-block elements. The polynomial version of the Generator Coordinate Dirac–Fock (p-GCDF) method is employed, along with multireference configuration interaction calculations with single and double substitutions (MR-CISD), to obtain correlation/polarization functions. Augmented versions containing additional diffuse functions for all orbital symmetries (aug-RPF-2Z and aug-RPF-3Z) are also provided. The quality of the basis sets was adequately validated through relativistic coupled-cluster calculations performed for equilibrium bond lengths, harmonic vibrational frequencies, and dipole moments of selected diatomic systems. The comparative analysis reveals some computational efficiency advantages with respect to traditional sets of similar sizes, such as dyall.v2z and dyall.v3z.